Shear and extensional rheology of commercial thickeners used for dysphagia management. Issue 6 (2nd May 2017) - Waqas, Muhammad Qazi; Wiklund, Johan; Altskär, Annika; Ekberg, Olle; Stading, Mats
Abstract: People who suffer from swallowing disorders, commonly referred to as dysphagia, are often restricted to a texture‐modified diet. In such a diet, the texture of the fluid is modified mainly by the addition of gum or starch‐based thickeners. For optimal modification of the texture, tunable rheological parameters are shear viscosity, yield stress, and elasticity. In this work, the flow properties of commercial thickeners obtained from major commercial suppliers were measured both in shear and extensional flow using a laboratory viscometer and a newly developed tube viscometry technique, termed Pulsed Ultrasound Velocimetry plus Pressure Drop (PUV + PD). The two methods gave similar results, demonstrating that the PUV + PD technique can be applied to study flow during the swallowing process in geometry similar to that of the swallowing tract. The thickeners were characterized in relation to extensional viscosity using the Hyperbolic Contraction Flow method, with microscopy used as a complementary method for visualization of the fluid structure. The gum‐based thickeners had significantly higher extensional viscosities than the starch‐based thickeners. The rheological behavior was manifested in the microstructure as a hydrocolloid network with dimensions in the nanometer range for the gum‐based thickeners. The starch‐based thickeners displayed a granular structure in the micrometer range. In addition, the commercial thickeners were compared to model fluids (Boger, Newtonian, and Shear‐thinning) set to equal shear viscosity at 50/s and it was demonstrated that their rheological behavior could be tuned between highly elastic, extension‐thickening to Newtonian. Practical applications: Thickeners available for dysphagia management were characterized for extensional viscosity to improve the understanding of these thickeners in large scale deformation. Extensional deformation behavior was further explained by using microcopy as corresponding technique for better understanding of structure/rheology relationship. Moreover, the major challenge in capturing human swallowing process is the short transit times of the bolus flow (<1 s). Therefore, the ultrasound‐based rheometry method; PUV+PD which measures the real‐time flow curve in ∼50 ms was used in addition to classical shear rheometry. The two methods complimented each other indicating that the PUV+PD method can be applied to study the transient swallowing process which is part of our future research, where we are studying the flow properties of fluids in an in vitro swallowing tract.